2016
DOI: 10.1590/0100-2945-288/14
|View full text |Cite
|
Sign up to set email alerts
|

DESENVOLVIMENTO INICIAL DE MUDAS DE Euterpe ssp. APÓS A APLICAÇÃO DE HERBICIDAS

Abstract: RESUMO -), além de uma testemunha sem aplicação de herbicida. a pulverização foi realizada sobre as mudas que apresentavam altura entre 45 e 50 cm. Foram realizadas avaliações visuais de fitotoxidade, altura das plantas aos 7; 14; 21; 28; 35; 42 e 49 dias após a aplicação (DAA)e ao final a massa seca da parte aérea.Visualmente, todos os herbicidas testados foram seletivos às duas espécies de palmeiras estudadas e quando ocorreram sintomas de injúrias(máximo 14%), estes dissiparam-se aos 49 daa. ao analisar-se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…It is noteworthy that in the second study, the dry mass increased with the application of the herbicides quizalofop-p-ethyl and nicosulfuron. A previous study (QUEIROZ et al, 2016) examined Euterpes edulis (açaí palm) seedlings that were treated with the same herbicides studied herein, and their results showed that sethoxydim did not reduce the height or accumulation of dry mass in plant shoots, as was also observed in the present study.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…It is noteworthy that in the second study, the dry mass increased with the application of the herbicides quizalofop-p-ethyl and nicosulfuron. A previous study (QUEIROZ et al, 2016) examined Euterpes edulis (açaí palm) seedlings that were treated with the same herbicides studied herein, and their results showed that sethoxydim did not reduce the height or accumulation of dry mass in plant shoots, as was also observed in the present study.…”
Section: Resultssupporting
confidence: 84%
“…This result might have been related to the age of the seedlings used in the second study, which were a little older. Queiroz et al (2016) evaluated the selectivity of herbicides in Euterpes oleracea (açaí palm) seedlings, using the same herbicides as the present study, and found that although the plants showed mild signs of damage, these were no longer observed at 49 DAS, as was found in the present study.…”
Section: Resultssupporting
confidence: 61%
“…Moreover, Queiroz et al (2016c) tested the same herbicides of the previous study, but with monosodium methanearsonate (MSMA) on assai palm (Euterpe oleracea Mart.) and jussara palm (E. edulis Mart.…”
Section: Palm Treesmentioning
confidence: 99%